A high-toughness packaging film and its preparation method
Through the synergistic effect of the composite toughening agent and modified montmorillonite filler in the polylactic acid packaging film, the problems of poor toughness and insufficient thermal stability of the polylactic acid packaging film are solved, and high toughness, strong mechanical properties and excellent results are achieved Preparation of thermally stable packaging film.
Patent Information
- Application Number
- CN202411337139.5
- Authority / Receiving Office
- CN · China
- Patent Type
- Patents(China)
- Current Assignee / Owner
- Filing Date
- 2024-09-25
- Publication Date
- 2025-02-18
- Estimated Expiration
- 2044-09-25
AI Technical Summary
The existing polylactic acid packaging film has poor toughness and high brittleness, making it difficult to meet the packaging needs of high toughness and impact resistance, and its thermal stability is also poor.
A composite toughening agent and modified montmorillonite filler are used to prepare a high-strength packaging film. The composite toughening agent is chemically bonded to soybean oil-based polyol through the chemical bonding of carbon nanotubes to form a composite structure with high strength and high ductility; the modified montmorillonite is modified by epoxypropyl trimethylammonium chloride and DOPO. Improves its thermal stability and flame retardant properties.
The toughness, mechanical properties and thermal stability of polylactic acid packaging film are significantly improved, the limitations of single component modification are overcome, and the synergistic efficiency between each component is achieved.
Smart Images

Figure BDA0005058568240000161
Abstract
Description
Technical Field
[0001] The present invention relates to the technical field of packaging film preparation, and in particular to a high-toughness packaging film and a preparation method thereof. Background Art
[0002] With the improvement of people's living standards and the enhancement of environmental awareness, degradable plastic packaging materials have received more and more attention. Among the many degradable plastics, polylactic acid (PLA) stands out with its unique advantages. PLA is a bio-based material made by fermentation of renewable resources (such as corn, cassava, etc.), with good biodegradability and renewability. It can not only effectively reduce dependence on petroleum resources, but also completely degrade in the natural environment, and finally convert into carbon dioxide and water, without causing long-term pollution to the environment. In addition, PLA also has excellent transparency, printability and processing properties, which make it show broad application prospects in food packaging, daily necessities packaging and other fields. However, despite the many advantages of PLA, its inherent defects cannot be ignored. The main problem of PLA is poor toughness and high brittleness, which makes packaging materials made of PLA easy to crack or break during transportation and use. This shortcoming seriously limits the application of PLA in packaging fields that require high toughness and impact resistance; in addition, the thermal stability of PLA is relatively poor, which further restricts its use in some special packaging fields.
[0003] The existing patent CN201710578905.0 discloses a high-barrier toughened polylactic acid film and its preparation method, which includes: obtaining layered dihydroxy metal oxides (LDHs) by a high-temperature hydrothermal method. Disperse the LDHs in water, add a tannic acid aqueous solution, and after adsorption, add an iron salt solution to obtain a reaction solution to quickly obtain modified LDHs (LDHs@TA-Fe(Ⅲ)). Disperse the modified LDHs in dimethylformamide, add polylactic acid, heat and stir to dissolve, then transfer to a film-forming device and dry to form a film. Tannic acid (TA) and iron ions are adsorbed, deposited and chelated on the surface of LDHs to form TA-Fe 3+ The core-shell structure of LDHs is coated, and the obtained polylactic acid film shows significant barrier and toughening effects. LDHs@TA-Fe(Ⅲ) and PLA show better compatibility and interfacial effects, which improves the performance of PLA. However, in the above technical solution, a single modified LDHs is used as a toughening agent, and its toughening effect is limited, which is difficult to meet the needs of high-toughness packaging applications; at the same time, the function of LDHs is relatively single, mainly used for toughening and improving barrier properties, and the improvement effect on other important properties of PLA, such as mechanical properties and thermal stability, is not ideal, thus limiting the application of existing technologies in the preparation of high-performance PLA packaging films. Summary of the invention
[0004] In view of this, the present invention proposes a high-toughness packaging film and a preparation method thereof to solve the technical problems in the prior art that the toughening effect of the packaging film is limited, and the mechanical properties and thermal stability are not ideal.
[0005] The technical solution of the present invention is achieved in this way:
[0006] In one aspect, the present invention provides a high-toughness packaging film, comprising the following raw materials in parts by weight: 65-85 parts of polylactic acid, 3-12 parts of a composite toughening agent, 1-5 parts of a modified montmorillonite filler, 0.5-2 parts of a lubricant, and 0.5-1 parts of an antioxidant.
[0007] On the basis of the above technical solution, preferably, the preparation method of the composite toughening agent comprises the following steps:
[0008] S1, acidifying and pretreating the carbon nanotubes, adding the pretreated carbon nanotubes and dopamine to a Tris-HCl aqueous solution, mixing, and reacting under ultrasonic stirring at room temperature for 16-24 hours, and centrifuging, washing, and vacuum drying the reaction product to obtain polydopamine-modified carbon nanotubes;
[0009] S2, dispersing 1,5-naphthalene diisocyanate in DMF, stirring at 60-70°C, slowly dropping the DMF solution of soybean oil-based polyol, controlling the dropping time to be 30-60min, and continuing the reaction for 1-2h. After the reaction is completed, washing, centrifuging and drying the reaction product to obtain isocyanate-based soybean oil;
[0010] S3. Disperse dopamine-modified carbon nanotubes in DMF, ultrasonically treat for 20-30 minutes, then add isocyanate-based soybean oil, stir evenly, then add dibutyltin dilaurate as a catalyst, and under nitrogen protection, stir the reaction mixture in an oil bath at 60-70°C for 4-6 hours. After the reaction is completed, cool the reaction mixture to room temperature, filter, wash and dry to obtain a composite toughening agent.
[0011] On the basis of the above technical scheme, preferably, in step S1, the acidification pretreatment of the carbon nanotubes specifically includes: placing the carbon nanotubes in a mixed solution of concentrated sulfuric acid and concentrated nitric acid in a volume ratio of 3:1, stirring the reaction at 60-70°C for 4-6 hours, and after the reaction is completed, cooling the reaction product to room temperature, diluting it with deionized water, and then collecting the solid by suction filtration, repeatedly washing it with deionized water until it is neutral, and vacuum drying it at 50-60°C for 12 hours to obtain pretreated carbon nanotubes.
[0012] In the present invention, in step S1, oxygen-containing functional groups such as carboxyl groups are introduced on the surface of carbon nanotubes by acidification treatment, and then a coating is formed on the surface of carbon nanotubes by self-polymerization reaction of polydopamine, wherein the acidification treatment can increase the hydrophilicity and reactivity of carbon nanotubes, reduce the tendency to agglomerate, and promote the adsorption and uniform coating of polydopamine on the surface of carbon nanotubes. In step S2, the isocyanate group (-N=C=O) in 1,5-naphthalene diisocyanate reacts with the hydroxyl group (-OH) in soybean oil-based polyol to introduce isocyanate groups into the soybean oil-based polyol molecules. In step S3, the isocyanate group in isocyanate soybean oil reacts with the amino group (-NH 2 ) or hydroxyl (-OH) reaction, prompting carbon nanotubes to connect with soybean oil base through chemical bonds to form a stable composite structure. Among them, carbon nanotubes provide rigid skeleton and high strength, while soybean oil-based polyols contribute flexible segments and high ductility. The two work together to form a composite structure with both strength and toughness, thereby improving the comprehensive mechanical properties of the packaging film, including tensile strength, elongation at break and toughness; at the same time, soybean oil-based polyols act as a "bridge" to connect carbon nanotubes and polylactic acid matrix, improving the dispersion of carbon nanotubes in polylactic acid and interface bonding strength.
[0013] On the basis of the above technical solution, preferably, in step S1, the mass ratio of the pretreated carbon nanotubes to dopamine is 1:(2-4), the Tris-HCl aqueous solution is obtained by mixing tris(hydroxymethylaminomethane), hydrochloric acid solution and deionized water, and the pH of the Tris-HCl aqueous solution is 8-10.
[0014] On the basis of the above technical scheme, preferably, in step S2, the preparation method of soybean oil-based polyol includes: mixing hydrochloric acid and acetone, adding epoxidized soybean oil dropwise at room temperature, stirring and dissolving for 15-20 minutes, heating to 40-50°C and stirring to react for 1.5-2.5 hours, after the reaction is completed, extracting the reaction product, and then washing, drying, and distilling under reduced pressure to obtain soybean oil-based polyol; the mass ratio of the epoxidized soybean oil to the hydrochloric acid is 3:1.8-2.2.
[0015] Based on the above technical solution, preferably, in step S2, the mass ratio of soybean oil-based polyol to 1,5-naphthalene diisocyanate is 1:1.5-2; in step S3, the mass ratio of dopamine-modified carbon nanotubes, isocyanate-based soybean oil and dibutyltin dilaurate is 1:2-3:0.2-0.4.
[0016] On the basis of the above technical solution, preferably, the preparation method of the modified montmorillonite filler comprises the following steps:
[0017] A1. Dispersing montmorillonite in a mixed solvent of water and ethanol, adding epoxypropyltrimethylammonium chloride, reacting at 60-80° C. for 1-3 hours, and centrifuging and drying the reaction product to obtain an organic modified montmorillonite;
[0018] A2, dispersing the organic modified montmorillonite in DMF, ultrasonically dispersing for 20-30 min, adding 9,10-dihydro-9-oxa-10-phosphaphenanthrene-10-oxide, heating to 80-120° C. under nitrogen protection, stirring and reacting for 8-12 h, after the reaction, cooling the reaction product to room temperature, centrifuging, washing and vacuum drying to obtain DOPO modified montmorillonite;
[0019] A3. Disperse DOPO modified montmorillonite in DMF, add azelaic acid and concentrated sulfuric acid, heat to 70-90°C, react for 4-6 hours. After the reaction, cool the reaction mixture to room temperature, filter, wash and dry to obtain modified montmorillonite filler.
[0020] In the present invention, montmorillonite can improve the thermal deformation temperature and thermal decomposition temperature of the packaging film, enhance the stability of the material in a high temperature environment, and also improve the gas and water vapor barrier properties of the packaging film. In step A1, epoxypropyl trimethyl ammonium chloride reacts with the inorganic cations between the montmorillonite layers, prompting them to be inserted into the interlayers of the montmorillonite and expand the interlayer distance of the montmorillonite; at the same time, the epoxy group is introduced to provide a reactive group for subsequent reactions. In step A2, 9,10-dihydro-9-oxa-10-phosphaphenanthrene-10-oxide (DOPO) reacts with the epoxy group introduced in step A1, so that the DOPO molecule is covalently bonded to the surface and interlayer of the montmorillonite. The phosphorus-oxygen structure in the DOPO molecule has an excellent flame retardant effect, and its grafting gives the final material flame retardant properties and improves the thermal stability of the packaging film; at the same time, the secondary modification increases the possibility of partial montmorillonite layer peeling, increases the specific surface area of montmorillonite, is conducive to improving the dispersibility of montmorillonite in the polymer, and may also enhance its gas barrier effect. In step A3, the hydroxyl group in the DOPO-modified montmorillonite reacts with the carboxyl group of azelaic acid, and the long-chain structure further enhances the organic compatibility and hydrophobicity of the montmorillonite. At the same time, by introducing long-chain carboxyl groups, the steric hindrance of the modified montmorillonite can be reduced, which is beneficial for the formation of covalent bonds between the hydroxyl long-chain carboxyl groups and the residual isocyanate groups in the composite toughening agent, thereby improving the interfacial bonding force between the modified montmorillonite filler and the composite toughening agent, and effectively improving the mechanical properties of the material.
[0021] On the basis of the above technical scheme, preferably, in step A1, the mass ratio of montmorillonite and epoxypropyltrimethylammonium chloride is 1:0.4-0.6; in step A2, the mass ratio of organic modified montmorillonite and 9,10-dihydro-9-oxa-10-phosphaphenanthrene-10-oxide is 1:0.2-0.4; in step A3, the mass ratio of DOPO modified montmorillonite, azelaic acid and concentrated sulfuric acid is 1:0.1-0.2:0.01-0.02.
[0022] Based on the above technical solution, preferably, the lubricant is any one of oleamide, butyl stearate and polyethylene wax, and the antioxidant is antioxidant 1010 or antioxidant 1076.
[0023] The present invention provides a method for preparing a high-toughness packaging film, and the method for preparing the high-toughness packaging film comprises the following steps:
[0024] Polylactic acid, composite toughening agent, modified montmorillonite filler, lubricant and antioxidant are weighed according to weight, mixed evenly, and extruded and granulated by a twin-screw granulator at a temperature of 170-190° C. to obtain high-toughness pellets; the high-toughness pellets are made into packaging films by a film blowing machine.
[0025] The high-toughness packaging film and the preparation method thereof of the present invention have the following beneficial effects compared with the prior art:
[0026] (1) The high-toughness packaging film provided by the present invention improves the toughness, mechanical properties and thermal stability of the polylactic acid packaging film through the synergistic effect of multiple components such as the composite toughening agent and the modified montmorillonite filler, which not only overcomes the limitation of single component modification, but also achieves synergistic enhancement between the components. The carbon nanotubes in the composite toughening agent and the modified montmorillonite filler form a double nano-reinforced network structure. The carbon nanotubes provide high strength and conductivity, while the montmorillonite provides excellent thermal stability. The interpenetrating network structure formed by the two in the polylactic acid matrix not only significantly improves the mechanical properties of the material, but also enhances the thermal stability through the synergistic effect; the soybean oil-based polyol component in the composite toughening agent and the organic modified layer of the modified montmorillonite jointly improve the dispersibility and interface compatibility of the filler in the polylactic acid, further enhancing the toughness and overall performance of the material;
[0027] (2) Through the acid pretreatment of carbon nanotubes and polydopamine modification, combined with the chemical bonding of isocyanate-based soybean oil, the composite toughening agent formed combines the high strength of carbon nanotubes and the high ductility of soybean oil-based polyols, which not only significantly improves the toughness and impact resistance of polylactic acid, but also improves the dispersibility and interfacial bonding strength of carbon nanotubes in polylactic acid by using the soybean oil-based structure as a "bridge", achieving the synergistic effect of rigidity enhancement and flexibility toughening, and effectively overcoming the negative impact of traditional toughening agents on material strength;
[0028] (3) Through organic modification with epoxypropyltrimethylammonium chloride and DOPO modification, the multifunctional modification of montmorillonite is achieved, which significantly improves the compatibility between montmorillonite and polylactic acid and also gives the material excellent thermal stability. At the same time, the modification process may cause partial montmorillonite to be stripped, increasing its specific surface area, further enhancing the gas barrier effect and the strengthening effect on the polymer matrix, so that montmorillonite can not only improve the mechanical properties of the packaging film, but also significantly improve its barrier properties and thermal stability. DETAILED DESCRIPTION
[0029] The following will be combined with the embodiments of the present invention to clearly and completely describe the technical solutions in the embodiments of the present invention. Obviously, the described embodiments are only part of the embodiments of the present invention, not all of the embodiments. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without creative work are within the scope of protection of the present invention.
[0030] Unless otherwise specified, the raw materials used in the following examples and comparative examples are all commercially available.
[0031] Polylactic acid was purchased from Shanghai Yuanye Biotechnology Co., Ltd., with a molecular weight of 60,000 and a product number of S30789; carbon nanotubes were purchased from Shanghai Yuanye Biotechnology Co., Ltd., with a diameter of 20-40 nm and a length of 1-5 μm, and a product number of T19281; montmorillonite was sodium montmorillonite, purchased from Shanghai Yuanye Biotechnology Co., Ltd., with a specific surface area of 240 m 2 / kg, item number is S42017.
[0032] Example 1
[0033] This embodiment provides a high-toughness packaging film and a preparation method thereof, which specifically comprises the following steps:
[0034] (1) According to weight, 750 g of polylactic acid, 80 g of composite toughening agent, 30 g of modified montmorillonite filler, 13 g of oleamide and 10108 g of antioxidant were weighed and mixed evenly.
[0035] Wherein, the preparation method of the composite toughening agent is as follows:
[0036] S1. Place 10 g of carbon nanotubes in a mixed solution of concentrated sulfuric acid (mass fraction 98%) and concentrated nitric acid (mass fraction 60%) in a volume ratio of 3:1, and stir the mixture at 65°C for 5 h. After the reaction is completed, cool the reaction product to room temperature, dilute it with deionized water, and then collect the solid by suction filtration, repeatedly wash it with deionized water until it is neutral, and vacuum dry it at 55°C for 12 h to obtain pretreated carbon nanotubes.
[0037] 6.1 g of tris (hydroxymethyl) aminomethane (Tris) was added to 5 L of deionized water, and magnetic stirring was performed at room temperature to completely dissolve it. A 1 mol / L hydrochloric acid solution (HCl) was added to the obtained solution to adjust the pH to obtain a Tris-HCl aqueous solution with a pH of 9. 10 g of pretreated carbon nanotubes and 30 g of dopamine were added to 400 mL of Tris-HCl aqueous solution, and the pH value of the Tris-HCl aqueous solution was 9. The mixture was stirred with ultrasonic stirring at room temperature for 20 h. The reaction product was centrifuged, washed, and vacuum dried to obtain polydopamine-modified carbon nanotubes;
[0038] S2, 20g hydrochloric acid and 110mL acetone were mixed, 30g epoxidized soybean oil was added dropwise at room temperature, stirred and dissolved for 20min, the temperature was raised to 45°C and stirred for reaction for 2h, after the reaction was completed, the reaction product was poured into a separatory funnel, ethyl acetate and water were added for extraction, and then the organic layer was washed with sodium bicarbonate solution, dried with magnesium sulfate for 24h, and the final product was distilled under reduced pressure to remove the solvent to obtain soybean oil-based polyol;
[0039] 18 g of 1,5-naphthalene diisocyanate was dispersed in 100 mL of DMF, and the mixture was stirred at 65° C. Then, a DMF solution of soybean oil-based polyol (10 g of soybean oil-based polyol was dissolved in 100 mL of DMF solution) was slowly added dropwise, and the addition time was controlled to be 45 min. The reaction was continued for 1.5 h. After the reaction was completed, the reaction product was washed, centrifuged and dried to obtain isocyanate-based soybean oil.
[0040] S3, 10g dopamine modified carbon nanotubes were dispersed in 100mL DMF, ultrasonically treated for 25min, then 25g isocyanate soybean oil was added, stirred evenly, and then 3g dibutyltin dilaurate was added as a catalyst. Under nitrogen protection, the reaction mixture was stirred in a 65℃ oil bath for 4h. After the reaction, the mixture was naturally cooled to room temperature, and then poured into a large amount of deionized water and stirred, and the solid product was collected by suction filtration. The product was washed with deionized water and ethanol for 3-5 times in sequence to remove unreacted raw materials and by-products. Finally, the washed product was placed in a 55℃ vacuum drying oven and dried for 18h to constant weight to obtain a composite toughening agent.
[0041] The preparation method of modified montmorillonite filler is as follows:
[0042] A1. Disperse 10g of montmorillonite in 100mL of a mixed solvent of water and ethanol (the ratio of water to ethanol is 3:1), disperse 5g of glycidyl trimethyl ammonium chloride in 50mL of a mixed solvent of water and ethanol, then drop the glycidyl trimethyl ammonium chloride solution into the montmorillonite dispersion, react at 70°C for 2h, after the reaction is completed, centrifuge the product, and wash it alternately with deionized water and ethanol for 3-5 times. The washed product is vacuum dried at 55°C for 18h to obtain an organic modified montmorillonite;
[0043] A2. Disperse 10g of organic modified montmorillonite in 100mL DMF, ultrasonically disperse for 25min, add 3g of 9,10-dihydro-9-oxa-10-phosphaphenanthrene-10-oxide in sequence, heat to 100°C under nitrogen protection, stir and react for 10h. After the reaction, cool the mixture naturally to room temperature, and then collect the solid product by centrifugation. Wash the product alternately with DMF and ethanol 3-5 times to remove unreacted raw materials. Finally, place the washed product in a 55°C vacuum drying oven and dry for 36h to constant weight to obtain DOPO modified montmorillonite;
[0044] A3. Disperse 10 g of DOPO-modified montmorillonite in DMF, add 1.5 g of azelaic acid and 0.15 g of concentrated sulfuric acid, heat to 80°C, and react for 5 h. After the reaction, cool the reaction mixture to room temperature, filter, wash, and dry to obtain a modified montmorillonite filler.
[0045] (2) The mixture is extruded and granulated by a twin-screw granulator at a temperature of 180° C. and a pressure of 2 MPa to obtain high-toughness granules; the high-toughness granules are formed into packaging films by a film blowing machine.
[0046] Example 2
[0047] This embodiment provides a high-toughness packaging film and a preparation method thereof, which specifically comprises the following steps:
[0048] (1) Weigh 650 g of polylactic acid, 30 g of composite toughening agent, 10 g of modified montmorillonite filler, 5 g of oleamide and 10105 g of antioxidant according to weight and mix them evenly.
[0049] Wherein, the preparation method of the composite toughening agent is as follows:
[0050] S1. Place 10 g of carbon nanotubes in a mixed solution of concentrated sulfuric acid (mass fraction 98%) and concentrated nitric acid (mass fraction 60%) in a volume ratio of 3:1, and stir the mixture at 60°C for 6 hours. After the reaction is completed, cool the reaction product to room temperature, dilute it with deionized water, and then collect the solid by suction filtration, repeatedly wash it with deionized water until it is neutral, and vacuum dry it at 50°C for 12 hours to obtain pretreated carbon nanotubes;
[0051] 6.1 g of tris (hydroxymethyl) aminomethane (Tris) was added to 5 L of deionized water, and magnetic stirring was performed at room temperature to completely dissolve it. A 1 mol / L hydrochloric acid solution (HCl) was added to the obtained solution to adjust the pH to obtain a Tris-HCl aqueous solution with a pH of 8-10. 10 g of pretreated carbon nanotubes and 20 g of dopamine were added to 300 mL of Tris-HCl aqueous solution, and the pH value of the Tris-HCl aqueous solution was 8. The mixture was stirred with ultrasonic stirring at room temperature for 24 h. The reaction product was centrifuged, washed, and vacuum dried to obtain polydopamine-modified carbon nanotubes;
[0052] S2, 18g hydrochloric acid and 100mL acetone were mixed, 30g epoxidized soybean oil was added dropwise at room temperature, stirred and dissolved for 15min, the temperature was raised to 40°C and stirred for reaction for 2.5h, after the reaction was completed, the reaction product was poured into a separatory funnel, ethyl acetate and water were added for extraction, and then the organic layer was washed with sodium bicarbonate solution, dried with magnesium sulfate for 24h, and the final product was distilled under reduced pressure to remove the solvent to obtain soybean oil-based polyol;
[0053] Disperse 15 g of 1,5-naphthalene diisocyanate in 100 mL of DMF, stir at 60° C. Slowly drop a DMF solution of soybean oil-based polyol (10 g of soybean oil-based polyol is dissolved in 100 mL of DMF solution), control the dropwise addition time to 30 min, and continue the reaction for 2 h. After the reaction is completed, wash, centrifuge and dry the reaction product to obtain isocyanate-based soybean oil;
[0054] S3, 10g dopamine modified carbon nanotubes were dispersed in 100mL DMF, ultrasonically treated for 20min, then 20g isocyanate soybean oil was added, stirred evenly, and then 2g dibutyltin dilaurate was added as a catalyst. Under nitrogen protection, the reaction mixture was stirred in a 60°C oil bath for 5h. After the reaction, the mixture was naturally cooled to room temperature, and then poured into a large amount of deionized water and stirred, and the solid product was collected by suction filtration. The product was washed with deionized water and ethanol for 3-5 times in sequence to remove unreacted raw materials and by-products. Finally, the washed product was placed in a 50°C vacuum drying oven and dried for 24h to constant weight to obtain a composite toughening agent.
[0055] The preparation method of modified montmorillonite filler is as follows:
[0056] A1. Disperse 10g of montmorillonite in 100mL of a mixed solvent of water and ethanol (the ratio of water to ethanol is 3:1), disperse 4g of glycidyl trimethyl ammonium chloride in 40mL of a mixed solvent of water and ethanol, then drop the glycidyl trimethyl ammonium chloride solution into the montmorillonite dispersion, react at 60°C for 3h, after the reaction is completed, centrifuge the product, and wash it alternately with deionized water and ethanol for 3-5 times. Dry the washed product in vacuum at 55°C for 18h to obtain an organic modified montmorillonite;
[0057] A2. Disperse 10g of organic modified montmorillonite in 100mL DMF, ultrasonically disperse for 20min, add 2g of 9,10-dihydro-9-oxa-10-phosphaphenanthrene-10-oxide in sequence, heat to 80°C under nitrogen protection, stir and react for 12h. After the reaction, cool the mixture naturally to room temperature, and then collect the solid product by centrifugation. Wash the product alternately with DMF and ethanol 3-5 times to remove unreacted raw materials. Finally, place the washed product in a 55°C vacuum drying oven and dry for 36h to constant weight to obtain DOPO modified montmorillonite;
[0058] A3. Disperse 10 g of DOPO modified montmorillonite in DMF, add 1 g of azelaic acid and 0.1 g of concentrated sulfuric acid, heat to 70°C, react for 6 h. After the reaction, cool the reaction mixture to room temperature, filter, wash, and dry to obtain a modified montmorillonite filler.
[0059] (2) The mixture is extruded and granulated by a twin-screw granulator at a temperature of 170° C. and a pressure of 3 MPa to obtain high-toughness granules; the high-toughness granules are formed into packaging films by a film blowing machine.
[0060] Example 3
[0061] This embodiment provides a high-toughness packaging film and a preparation method thereof, which specifically comprises the following steps:
[0062] (1) According to weight, 850 g of polylactic acid, 120 g of composite toughening agent, 50 g of modified montmorillonite filler, 20 g of oleamide and 101010 g of antioxidant were weighed and mixed evenly.
[0063] Wherein, the preparation method of the composite toughening agent is as follows:
[0064] S1. Place 10 g of carbon nanotubes in a mixed solution of concentrated sulfuric acid (98% by mass) and concentrated nitric acid (60% by mass) in a volume ratio of 3:1, and stir the mixture at 70°C for 4 h. After the reaction is completed, cool the reaction product to room temperature, dilute it with deionized water, collect the solid by suction filtration, repeatedly wash it with deionized water until it is neutral, and vacuum dry it at 60°C for 12 h to obtain pretreated carbon nanotubes.
[0065] 6.1 g of tris (hydroxymethyl) aminomethane (Tris) was added to 5 L of deionized water, and magnetic stirring was performed at room temperature to completely dissolve it. A 1 mol / L hydrochloric acid solution (HCl) was added to the obtained solution to adjust the pH to obtain a Tris-HCl aqueous solution with a pH of 8-10. 10 g of pretreated carbon nanotubes and 40 g of dopamine were added to 500 mL of Tris-HCl aqueous solution, the pH value of the Tris-HCl aqueous solution was 10, and the reaction was carried out under ultrasonic stirring at room temperature for 16 h. The reaction product was centrifuged, washed, and vacuum dried to obtain polydopamine-modified carbon nanotubes;
[0066] S2, 22g hydrochloric acid and 120mL acetone were mixed, 30g epoxidized soybean oil was added dropwise at room temperature, stirred and dissolved for 20min, the temperature was raised to 50°C and stirred for reaction for 1.5h, after the reaction was completed, the reaction product was poured into a separatory funnel, ethyl acetate and water were added for extraction, and then the organic layer was washed with sodium bicarbonate solution, dried with magnesium sulfate for 24h, and the final product was distilled under reduced pressure to remove the solvent to obtain soybean oil-based polyol;
[0067] 20 g of 1,5-naphthalene diisocyanate was dispersed in 100 mL of DMF, and the mixture was stirred at 70° C. Then, a DMF solution of soybean oil-based polyol (10 g of soybean oil-based polyol was dissolved in 100 mL of DMF solution) was slowly added dropwise, and the addition time was controlled to be 60 min. The reaction was continued for 1 h. After the reaction was completed, the reaction product was washed, centrifuged and dried to obtain isocyanate-based soybean oil.
[0068] S3, 10g dopamine modified carbon nanotubes were dispersed in 100mL DMF, ultrasonically treated for 30min, then 30g isocyanate soybean oil was added, stirred evenly, and then 4g dibutyltin dilaurate was added as a catalyst. Under nitrogen protection, the reaction mixture was stirred in a 70℃ oil bath for 3h. After the reaction, the mixture was naturally cooled to room temperature, and then poured into a large amount of deionized water and stirred, and the solid product was collected by suction filtration. The product was washed with deionized water and ethanol for 3-5 times in sequence to remove unreacted raw materials and by-products. Finally, the washed product was placed in a 60℃ vacuum drying oven and dried for 12h to constant weight to obtain a composite toughening agent.
[0069] The preparation method of modified montmorillonite filler is as follows:
[0070] A1. Disperse 10g of montmorillonite in 100mL of a mixed solvent of water and ethanol (the ratio of water to ethanol is 3:1), disperse 6g of glycidyl trimethyl ammonium chloride in 60mL of a mixed solvent of water and ethanol, then drop the glycidyl trimethyl ammonium chloride solution into the montmorillonite dispersion, react at 80°C for 1h, after the reaction is completed, centrifuge the product, and wash it alternately with deionized water and ethanol for 3-5 times. Dry the washed product in vacuum at 55°C for 18h to obtain an organic modified montmorillonite;
[0071] A2. Disperse 10g of organic modified montmorillonite in 100mL DMF, ultrasonically disperse for 25min, add 4g of 9,10-dihydro-9-oxa-10-phosphaphenanthrene-10-oxide in sequence, heat to 120°C under nitrogen protection, stir and react for 8h. After the reaction, cool the mixture naturally to room temperature, and then collect the solid product by centrifugation. Wash the product alternately with DMF and ethanol 3-5 times to remove unreacted raw materials. Finally, place the washed product in a 55°C vacuum drying oven and dry for 36h to constant weight to obtain DOPO modified montmorillonite;
[0072] A3. Disperse 10 g of DOPO-modified montmorillonite in DMF, add 2 g of azelaic acid and 0.2 g of concentrated sulfuric acid, heat to 90°C, and react for 4 h. After the reaction, cool the reaction mixture to room temperature, filter, wash, and dry to obtain a modified montmorillonite filler.
[0073] (2) The mixture is extruded and granulated by a twin-screw granulator at a temperature of 190° C. and a pressure of 1 MPa to obtain high-toughness granules; the high-toughness granules are formed into packaging films by a film blowing machine.
[0074] Example 4
[0075] This embodiment provides a high-toughness packaging film and a preparation method thereof, which specifically comprises the following steps:
[0076] (1) According to weight, 800 g of polylactic acid, 100 g of composite toughening agent, 20 g of modified montmorillonite filler, 15 g of oleamide and 10106 g of antioxidant were weighed and mixed evenly.
[0077] Wherein, the preparation method of the composite toughening agent is as follows:
[0078] S1. Place 10 g of carbon nanotubes in a mixed solution of concentrated sulfuric acid (mass fraction 98%) and concentrated nitric acid (mass fraction 60%) in a volume ratio of 3:1, and stir the reaction at 65°C for 4.5 hours. After the reaction is completed, cool the reaction product to room temperature, dilute it with deionized water, and then collect the solid by suction filtration, repeatedly wash it with deionized water until it is neutral, and vacuum dry it at 55°C for 12 hours to obtain pretreated carbon nanotubes;
[0079] 6.1 g of tris (hydroxymethyl) aminomethane (Tris) was added to 5 L of deionized water, and magnetic stirring was performed at room temperature to completely dissolve it. A 1 mol / L hydrochloric acid solution (HCl) was added to the obtained solution to adjust the pH to obtain a Tris-HCl aqueous solution with a pH of 10. 10 g of pretreated carbon nanotubes and 35 g of dopamine were added to 450 mL of Tris-HCl aqueous solution, and the pH value of the Tris-HCl aqueous solution was 10. The mixture was stirred with ultrasonic stirring at room temperature for 18 h. The reaction product was centrifuged, washed, and vacuum dried to obtain polydopamine-modified carbon nanotubes;
[0080] S2, 19g hydrochloric acid and 110mL acetone were mixed, 30g epoxidized soybean oil was added dropwise at room temperature, stirred and dissolved for 18min, the temperature was raised to 50°C and stirred for reaction for 1.5h, after the reaction was completed, the reaction product was poured into a separatory funnel, ethyl acetate and water were added for extraction, and then the organic layer was washed with sodium bicarbonate solution, dried with magnesium sulfate for 24h, and the final product was distilled under reduced pressure to remove the solvent to obtain soybean oil-based polyol;
[0081] 17 g of 1,5-naphthalene diisocyanate was dispersed in 100 mL of DMF, and the mixture was stirred at 70° C. A DMF solution of soybean oil-based polyol (10 g of soybean oil-based polyol was dissolved in 100 mL of DMF solution) was slowly added dropwise, and the addition time was controlled to be 35 min. The reaction was continued for 1.5 h. After the reaction was completed, the reaction product was washed, centrifuged and dried to obtain isocyanate-based soybean oil.
[0082] S3, 10g dopamine modified carbon nanotubes were dispersed in 100mL DMF, ultrasonically treated for 25min, then 24g isocyanate soybean oil was added, stirred evenly, and then 2.5g dibutyltin dilaurate was added as a catalyst. Under nitrogen protection, the reaction mixture was stirred in a 65℃ oil bath for 3.5h. After the reaction, the mixture was naturally cooled to room temperature, and then poured into a large amount of deionized water and stirred, and the solid product was collected by suction filtration. The product was washed with deionized water and ethanol for 3-5 times in sequence to remove unreacted raw materials and by-products. Finally, the washed product was placed in a 55℃ vacuum drying oven and dried for 20h to constant weight to obtain a composite toughening agent.
[0083] The preparation method of modified montmorillonite filler is as follows:
[0084] A1. Disperse 10g of montmorillonite in 100mL of a mixed solvent of water and ethanol (the ratio of water to ethanol is 3:1), disperse 3.5g of glycidyl trimethyl ammonium chloride in 50mL of a mixed solvent of water and ethanol, then drop the glycidyl trimethyl ammonium chloride solution into the montmorillonite dispersion, react at 75°C for 1.5h, after the reaction is completed, centrifuge the product, and wash it alternately with deionized water and ethanol for 3-5 times. Dry the washed product in vacuum at 55°C for 18h to obtain an organic modified montmorillonite;
[0085] A2. Disperse 10g of organic modified montmorillonite in 100mL DMF, ultrasonically disperse for 25min, add 3.5g of 9,10-dihydro-9-oxa-10-phosphaphenanthrene-10-oxide in sequence, heat to 105°C under nitrogen protection, stir and react for 9h. After the reaction, cool the mixture naturally to room temperature, and then collect the solid product by centrifugation. Wash the product alternately with DMF and ethanol 3-5 times to remove unreacted raw materials. Finally, place the washed product in a 55°C vacuum drying oven and dry for 36h to constant weight to obtain DOPO modified montmorillonite;
[0086] A3. Disperse 10 g of DOPO modified montmorillonite in DMF, add 1.2 g of azelaic acid and 0.18 g of concentrated sulfuric acid, heat to 85°C, react for 4.5 h. After the reaction, cool the reaction mixture to room temperature, filter, wash, and dry to obtain a modified montmorillonite filler.
[0087] (2) The mixture is extruded and granulated by a twin-screw granulator at a temperature of 180° C. and a pressure of 2 MPa to obtain high-toughness granules; the high-toughness granules are formed into packaging films by a film blowing machine.
[0088] Comparative Example 1
[0089] This comparative example provides a high-toughness packaging film and a preparation method thereof, which specifically comprises the following steps:
[0090] (1) According to weight, 750 g of polylactic acid, 80 g of composite toughening agent, 30 g of modified montmorillonite filler, 13 g of oleamide and 10108 g of antioxidant were weighed and mixed evenly.
[0091] Wherein, the preparation method of the composite toughening agent is as follows:
[0092] S1. Place 10 g of carbon nanotubes in a mixed solution of concentrated sulfuric acid (mass fraction 98%) and concentrated nitric acid (mass fraction 60%) in a volume ratio of 3:1, and stir the mixture at 65°C for 5 h. After the reaction is completed, cool the reaction product to room temperature, dilute it with deionized water, and then collect the solid by suction filtration, repeatedly wash it with deionized water until it is neutral, and vacuum dry it at 55°C for 12 h to obtain pretreated carbon nanotubes.
[0093] 6.1 g of tris (hydroxymethyl) aminomethane (Tris) was added to 5 L of deionized water, and magnetic stirring was performed at room temperature to completely dissolve it. A 1 mol / L hydrochloric acid solution (HCl) was added to the obtained solution to adjust the pH to obtain a Tris-HCl aqueous solution with a pH of 9. 10 g of pretreated carbon nanotubes and 30 g of dopamine were added to 400 mL of Tris-HCl aqueous solution, and the pH value of the Tris-HCl aqueous solution was 9. The mixture was stirred with ultrasonic stirring at room temperature for 20 h. The reaction product was centrifuged, washed, and vacuum dried to obtain polydopamine-modified carbon nanotubes, which were composite toughening agents.
[0094] The preparation method of modified montmorillonite filler is as follows:
[0095] A1. Disperse 10g of montmorillonite in 100mL of a mixed solvent of water and ethanol (the ratio of water to ethanol is 3:1), disperse 5g of glycidyl trimethyl ammonium chloride in 50mL of a mixed solvent of water and ethanol, then drop the glycidyl trimethyl ammonium chloride solution into the montmorillonite dispersion, react at 70°C for 2h, after the reaction is completed, centrifuge the product, and wash it alternately with deionized water and ethanol for 3-5 times. The washed product is vacuum dried at 55°C for 18h to obtain an organic modified montmorillonite;
[0096] A2. Disperse 10g of organic modified montmorillonite in 100mL DMF, ultrasonically disperse for 25min, add 3g of 9,10-dihydro-9-oxa-10-phosphaphenanthrene-10-oxide in sequence, heat to 100°C under nitrogen protection, stir and react for 10h. After the reaction, cool the mixture naturally to room temperature, and then collect the solid product by centrifugation. Wash the product alternately with DMF and ethanol 3-5 times to remove unreacted raw materials. Finally, place the washed product in a 55°C vacuum drying oven and dry for 36h to constant weight to obtain DOPO modified montmorillonite;
[0097] A3. Disperse 10 g of DOPO-modified montmorillonite in DMF, add 1.5 g of azelaic acid and 0.15 g of concentrated sulfuric acid, heat to 80°C, and react for 5 h. After the reaction, cool the reaction mixture to room temperature, filter, wash, and dry to obtain a modified montmorillonite filler.
[0098] (2) The mixture is extruded and granulated by a twin-screw granulator at a temperature of 180° C. and a pressure of 2 MPa to obtain high-toughness granules; the high-toughness granules are formed into packaging films by a film blowing machine.
[0099] Comparative Example 2
[0100] This embodiment provides a high-toughness packaging film and a preparation method thereof, which specifically comprises the following steps:
[0101] (1) According to weight, 750 g of polylactic acid, 80 g of composite toughening agent, 30 g of modified montmorillonite filler, 13 g of oleamide and 10108 g of antioxidant were weighed and mixed evenly.
[0102] Wherein, the preparation method of the composite toughening agent is as follows:
[0103] S1. Place 10 g of carbon nanotubes in a mixed solution of concentrated sulfuric acid (mass fraction 98%) and concentrated nitric acid (mass fraction 60%) in a volume ratio of 3:1, and stir the mixture at 65°C for 5 h. After the reaction is completed, cool the reaction product to room temperature, dilute it with deionized water, and then collect the solid by suction filtration, repeatedly wash it with deionized water until it is neutral, and vacuum dry it at 55°C for 12 h to obtain pretreated carbon nanotubes.
[0104] 6.1 g of tris (hydroxymethyl) aminomethane (Tris) was added to 5 L of deionized water, and magnetic stirring was performed at room temperature to completely dissolve it. A 1 mol / L hydrochloric acid solution (HCl) was added to the obtained solution to adjust the pH to obtain a Tris-HCl aqueous solution with a pH of 9. 10 g of pretreated carbon nanotubes and 30 g of dopamine were added to 400 mL of Tris-HCl aqueous solution, and the pH value of the Tris-HCl aqueous solution was 9. The mixture was stirred with ultrasonic stirring at room temperature for 20 h. The reaction product was centrifuged, washed, and vacuum dried to obtain polydopamine-modified carbon nanotubes;
[0105] S2, 20g hydrochloric acid and 110mL acetone were mixed, 30g epoxidized soybean oil was added dropwise at room temperature, stirred and dissolved for 20min, the temperature was raised to 45°C and stirred for reaction for 2h, after the reaction was completed, the reaction product was poured into a separatory funnel, ethyl acetate and water were added for extraction, and then the organic layer was washed with sodium bicarbonate solution, dried with magnesium sulfate for 24h, and the final product was distilled under reduced pressure to remove the solvent to obtain soybean oil-based polyol;
[0106] 18 g of 1,5-naphthalene diisocyanate was dispersed in 100 mL of DMF, and the mixture was stirred at 65° C. Then, a DMF solution of soybean oil-based polyol (10 g of soybean oil-based polyol was dissolved in 100 mL of DMF solution) was slowly added dropwise, and the addition time was controlled to be 45 min. The reaction was continued for 1.5 h. After the reaction was completed, the reaction product was washed, centrifuged and dried to obtain isocyanate-based soybean oil.
[0107] S3, 10g dopamine modified carbon nanotubes were dispersed in 100mL DMF, ultrasonically treated for 25min, then 25g isocyanate soybean oil was added, stirred evenly, and then 3g dibutyltin dilaurate was added as a catalyst. Under nitrogen protection, the reaction mixture was stirred in a 65℃ oil bath for 4h. After the reaction, the mixture was naturally cooled to room temperature, and then poured into a large amount of deionized water and stirred, and the solid product was collected by suction filtration. The product was washed with deionized water and ethanol for 3-5 times in sequence to remove unreacted raw materials and by-products. Finally, the washed product was placed in a 55℃ vacuum drying oven and dried for 18h to constant weight to obtain a composite toughening agent.
[0108] The preparation method of modified montmorillonite filler is as follows:
[0109] A1. Disperse 10g of montmorillonite in 100mL of a mixed solvent of water and ethanol (the ratio of water to ethanol is 3:1), disperse 5g of glycidyl trimethyl ammonium chloride in 50mL of a mixed solvent of water and ethanol, then drop the glycidyl trimethyl ammonium chloride solution into the montmorillonite dispersion, react at 70°C for 2h, after the reaction is completed, centrifuge the product, and wash it alternately with deionized water and ethanol for 3-5 times. The washed product is vacuum dried at 55°C for 18h to obtain an organic modified montmorillonite.
[0110] (2) The mixture is extruded and granulated by a twin-screw granulator at a temperature of 180° C. and a pressure of 2 MPa to obtain high-toughness granules; the high-toughness granules are formed into packaging films by a film blowing machine.
[0111] Performance Testing
[0112] The high-toughness packaging film samples prepared in the examples and comparative examples were subjected to performance tests, wherein the mechanical properties were tested on a universal testing machine according to the GB / T1040.3-2006 test standard; the tear resistance was tested according to QB / T1130-1991; the heat deformation temperature was tested according to ASTM E2092; the degradation rate was tested, that is, a 10×10 cm sample of the high-toughness packaging film was taken. 2 The size of the samples was buried in the soil for 3 weeks at a temperature of 25°C and a soil humidity of 25%. The mass before and after burial in the soil was weighed and the degradation rate was calculated. The test results are shown in Table 1.
[0113] Table 1 Performance test
[0114]
[0115] It can be seen from Table 1 that the high-toughness packaging film prepared by the preparation method of the present invention can have both good strength and toughness, and also has good thermal stability and degradation rate.
[0116] The above description is only a preferred embodiment of the present invention and is not intended to limit the present invention. Any modifications, equivalent substitutions, improvements, etc. made within the spirit and principles of the present invention should be included in the protection scope of the present invention.
Claims
1. A high-toughness packaging film, characterized in that: The invention comprises the following raw materials in parts by weight: 65-85 parts of polylactic acid, 3-12 parts of composite toughening agent, 1-5 parts of modified montmorillonite filler, 0.5-2 parts of lubricant and 0.5-1 parts of antioxidant; The preparation method of the composite toughening agent comprises the following steps: S1, acidifying and pretreating the carbon nanotubes, adding the pretreated carbon nanotubes and dopamine to a Tris-HCl aqueous solution, mixing, and reacting under ultrasonic stirring at room temperature for 16-24 hours, and centrifuging, washing, and vacuum drying the reaction product to obtain polydopamine-modified carbon nanotubes; S2, dispersing 1,5-naphthalene diisocyanate in DMF, stirring at 60-70°C, slowly dropping the DMF solution of soybean oil-based polyol, controlling the dropping time to be 30-60min, and continuing the reaction for 1-2h. After the reaction is completed, washing, centrifuging and drying the reaction product to obtain isocyanate-based soybean oil; S3, dispersing dopamine-modified carbon nanotubes in DMF, ultrasonically treating for 20-30 minutes, then adding isocyanate-based soybean oil, stirring evenly, then adding dibutyltin dilaurate as a catalyst, stirring the reaction mixture in an oil bath at 60-70°C for 3-5 hours under nitrogen protection, and after the reaction is completed, cooling the reaction mixture to room temperature, filtering, washing and drying to obtain a composite toughening agent; The preparation method of the modified montmorillonite filler comprises the following steps: A1. Dispersing montmorillonite in a mixed solvent of water and ethanol, adding epoxypropyltrimethylammonium chloride, reacting at 60-80° C. for 1-3 hours, and centrifuging and drying the reaction product to obtain an organic modified montmorillonite; A2, dispersing the organic modified montmorillonite in DMF, adding 9,10-dihydro-9-oxa-10-phosphaphenanthrene-10-oxide, heating to 80-120°C under nitrogen protection, stirring and reacting for 8-12h, after the reaction, cooling the reaction product to room temperature, centrifuging, washing and vacuum drying to obtain DOPO modified montmorillonite; A3. Disperse DOPO modified montmorillonite in DMF, add azelaic acid and concentrated sulfuric acid, heat to 70-90°C, react for 4-6 hours. After the reaction, cool the reaction mixture to room temperature, filter, wash and dry to obtain modified montmorillonite filler.
2. A high-toughness packaging film as claimed in claim 1, characterized in that: In step S1, the acidification pretreatment of the carbon nanotubes specifically includes: placing the carbon nanotubes in a mixed solution of concentrated sulfuric acid and concentrated nitric acid in a volume ratio of 3:1, stirring the reaction at 60-70°C for 4-6 hours, and after the reaction is completed, cooling the reaction product to room temperature, diluting it with deionized water, and then collecting the solid by suction filtration, repeatedly washing it with deionized water until it is neutral, and vacuum drying it at 50-60°C for 12 hours to obtain pretreated carbon nanotubes.
3. The high-toughness packaging film according to claim 1, characterized in that: In step S1, the mass ratio of the pretreated carbon nanotubes to dopamine is 1:(2-4), the Tris-HCl aqueous solution is obtained by mixing tris(hydroxymethylaminomethane), hydrochloric acid solution and deionized water, and the pH of the Tris-HCl aqueous solution is 8-10.
4. The high-toughness packaging film according to claim 1, characterized in that: In step S2, the preparation method of soybean oil-based polyol includes: mixing hydrochloric acid and acetone, adding epoxy soybean oil dropwise at room temperature, stirring and dissolving for 15-20 minutes, heating to 40-50°C and stirring for reaction for 1.5-2.5 hours, and after the reaction is completed, extracting the reaction product, and then washing, drying, and distilling under reduced pressure to obtain soybean oil-based polyol; the mass ratio of the epoxy soybean oil to the hydrochloric acid is 3:1.8-2.
2.
5. The high-toughness packaging film according to claim 1, characterized in that: In step S2, the mass ratio of soybean oil-based polyol to 1,5-naphthalene diisocyanate is 1:1.5-2; in step S3, the mass ratio of dopamine-modified carbon nanotubes, isocyanate-based soybean oil and dibutyltin dilaurate is 1:2-3:0.2-0.
4.
6. The high-toughness packaging film according to claim 1, characterized in that: In step A1, the mass ratio of montmorillonite to epoxypropyltrimethylammonium chloride is 1:0.4-0.6; in step A2, the mass ratio of organic modified montmorillonite to 9,10-dihydro-9-oxa-10-phosphaphenanthrene-10-oxide is 1:0.2-0.4; in step A3, the mass ratio of DOPO modified montmorillonite, azelaic acid and concentrated sulfuric acid is 1:0.1-0.2:0.01-0.
02.
7. The high-toughness packaging film according to claim 1, characterized in that: The lubricant is any one of oleamide, butyl stearate and polyethylene wax, and the antioxidant is antioxidant 1010 or antioxidant 1076.
8. A method for preparing a high-toughness packaging film according to any one of claims 1 to 7, characterized in that: The preparation method of the high-toughness packaging film comprises the following steps: Polylactic acid, composite toughening agent, modified montmorillonite filler, lubricant and antioxidant are weighed according to weight, mixed evenly, and extruded and granulated by a twin-screw granulator at a temperature of 170-190° C. to obtain high-toughness pellets; the high-toughness pellets are made into packaging films by a film blowing machine.
Citation Information
Patent Citations
A high-barrier toughened polylactic acid film and its preparation method
CN107254152B
Preparation method and application of manganese dioxide / silver composite nanometer material based on graphene / carbon nanometer tubes
CN107331872A
Functionalized carbon nanotube / polyurethane composite material and preparation method thereof
CN116217878A